Calcifying odontogenic cyst with ameloblastic fibro-odontome: one lesion or two? - Farman, A G; Smith, S N; Nortjé, C J; Grotepass, F W (Journal of oral pathology, 1978)
The calcifying odontogenic cyst is unusual in that it is frequently found in conjunction with the histologic features of a variety of other odontogenic conditions. Two cases are reported, one of which contained areas histologically similar to the ameloblastic fibro-odontome and also showed condensations of cells in the stroma beneath epithelial strands proliferating from the cyst lining. In both cases the "ghost cells" stained strongly for disulphide groups but only occasional areas were positive for sulphydryl groups. No amyloid or "amyloid-like" material was detected. As no part of the current name is specific to this lesion it is suggested that the nomenclature should be changed--perhaps to "ghost cell dyst".